Multi-variable models predicting specific patient-reported acute urinary symptoms after radiotherapy for prostate cancer: Results of a cohort study. Issue 2 (August 2015) - Cozzarini, Cesare; Rancati, Tiziana; Carillo, Viviana; Civardi, Francesco; Garibaldi, Elisabetta; Franco, Pierfrancesco; Avuzzi, Barbara; Esposti, Claudio Degli; Girelli, Giuseppe; Iotti, Cinzia; Palorini, Federica; Vavassori, Vittorio; et al.
Abstract Purpose A prospective trial started in 2010, aiming at developing models for urinary toxicity and erectile dysfunction after radiotherapy for prostate cancer. This analysis is finalised at highlighting correlations between clinical/dosimetric factors and acute urinary specific symptoms, as measured by single questions of the International Prostate Symptom Score (IPSS). Materials/methods IPSS was prospectively collected before and at the end of radiotherapy; absolute weekly bladder dose–surface histograms (DSHw) were chosen as dosimetric descriptors. Relevant clinical factors were prospectively gathered. Backward feature selection was used to identify variables to be included in logistic models for moderate–severe (scores ⩾ 4) urinary symptoms. Results Complete data of 262 patients (120 conventional fractionation, 142 hypofractionation) were available. Smoking was a strong predictor for feeling of incomplete emptying, frequency, intermittency, urgency and straining; neoadjuvant hormonal therapy and use of antihypertensive drugs were risk factors for intermittency and weak stream, respectively. The baseline score was a major predictor for all symptoms with the exception of intermittency. DSHw were correlated to increased risk of frequency, intermittency, urgency and nocturia. Most models showed moderate–high discrimination (AUC ≈ 0.60–0.79). Conclusions Smoking and other clinical and dosimetric factors predict for specific moderate–severe acute urinary symptoms; baseline condition heavily modulated the risk in most endpoints.